DYNAMICS OF THE SOCIOCULTURAL SPACE OF EDUCATION IN THE CONTEXT OF CRISIS PROCESSES IN UKRAINE - Ashytok , Nadiia (Proceedings of the National Aviation University Series Philosophy Cultural, 2024)
Introduction. Studying dynamic changes in the sociocultural dimension of education reform is a priority for understanding the strategy and direction of its development in crisis conditions. The aim of the article is to understand the development of the socio-cultural space of education in Ukraine in the context of crisis conditions. Research methods encompass general scientific and special methods, including theoretical analysis, systematization, comparison, and generalization. Research results. The socio-cultural unity of the world countries is manifested in the crisis characteristic of modern education, which is caused by the increasing gap between culture and education. The traditional education system uses fixed methods and rules designed to cope with already-known situations. Traditional education should be replaced by education aimed at training creative individuals who are able to solve problems in a non-standard way in situations of uncertainty. Modernization of education in crisis conditions is carried out with a dynamism that is not typical for its progressive development in peacetime, since the extremity of these conditions requires a quick and effective stabilization of education, ensuring its ability to perform its inherent functions and meet the requirements of modernity. It is necessary to carry out the modernization of education in parallel with the stabilization of other spheres of social life, in particular, culture. Discussion. Despite the indisputability of the existence of prefigurative cultures, the example of an electronic communication network, considered by M.Mead as a factor in the separation of generations within this culture, is currently unconvincing. Nowadays, this network has become a common sphere of communication for all strata of the population. For prefigurative cultures, the experience of elders is transferred to representatives of the younger generation to a much lesser extent, but this is not due to the means of communication, but to changes in the content and conditions of acquiring experience. Conclusion. The modernization of the sociocultural space of education in Ukraine in crisis conditions is determined both by urgent needs, aimed mainly at stabilizing education, and by the desire to meet world standards.